2012
DOI: 10.1029/2012gl053240
|View full text |Cite
|
Sign up to set email alerts
|

Sea level trends, interannual and decadal variability in the Pacific Ocean

Abstract: [1] Linear trend analysis is commonly applied to quantify sea level change, often over short periods because of limited data availability. However, the linear trend computed over short periods is complicated by large-scale climate variability which can affect regional sea level on interannual to inter-decadal time scales. As a result, the meaning of a local linear sea level trend over the short altimeter era (since 1993; less than 20 years) is unclear, and it is not straightforward to distinguish the regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
212
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(227 citation statements)
references
References 52 publications
14
212
0
1
Order By: Relevance
“…It is significantly correlated with ENSO (e.g., Alexander et al 2002;Newman et al 2003;Deser et al 2004;Schneider and Cornuelle 2005;Vimont 2005). On decadal timescales, the PDO is highly correlated with ENSO (Zhang and Church 2012) and the Interdecadal Pacific Oscillation (IPO), a basin-wide decadal climate mode associated with decadal SST variability in the Pacific (e.g., Power et al 1999;Folland et al 2002;Meehl and Hu 2006). The correlation coefficients for PDO-IPO and IPO-NINO3.4 indices (8-year low-passed) are both 0.88 over the period of 1900(Han et al 2014aZhang and Church 2012).…”
Section: Pdo-related Sea Level Patternsmentioning
confidence: 91%
See 3 more Smart Citations
“…It is significantly correlated with ENSO (e.g., Alexander et al 2002;Newman et al 2003;Deser et al 2004;Schneider and Cornuelle 2005;Vimont 2005). On decadal timescales, the PDO is highly correlated with ENSO (Zhang and Church 2012) and the Interdecadal Pacific Oscillation (IPO), a basin-wide decadal climate mode associated with decadal SST variability in the Pacific (e.g., Power et al 1999;Folland et al 2002;Meehl and Hu 2006). The correlation coefficients for PDO-IPO and IPO-NINO3.4 indices (8-year low-passed) are both 0.88 over the period of 1900(Han et al 2014aZhang and Church 2012).…”
Section: Pdo-related Sea Level Patternsmentioning
confidence: 91%
“…On decadal timescales, the PDO is highly correlated with ENSO (Zhang and Church 2012) and the Interdecadal Pacific Oscillation (IPO), a basin-wide decadal climate mode associated with decadal SST variability in the Pacific (e.g., Power et al 1999;Folland et al 2002;Meehl and Hu 2006). The correlation coefficients for PDO-IPO and IPO-NINO3.4 indices (8-year low-passed) are both 0.88 over the period of 1900(Han et al 2014aZhang and Church 2012). Given their high correlations on decadal timescales, it has been suggested that the IPO may not be confidently treated as an independent climate mode to ENSO decadal variability (e.g., Trenberth et al 2007) or that the PDO is a statistic mode rather than a physical mode with a single mechanism (see review by Newman et al 2016).…”
Section: Pdo-related Sea Level Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…5, 6) and observations (not shown) are dominated by ENSO and the IOD. It should be noted that this study does not seek to resolve lower frequency components of signals such as the PDO or NAO which also influence global and local sea levels (Zhang and Church 2012).…”
Section: Discussionmentioning
confidence: 99%